Communication That Gives Life to Leadership: An Exegetical Analysis of John 1:1–18 - Joseph Pastori (Religions, 2025)
The definitive demonstration of effective leadership is the ability to communicate with purpose in such a way that gives life to ideas and accomplishes organizational objectives. God’s message of grace to humanity was the Word, his Son Jesus Christ. God’s mode of communication is an example to us. As “The Word became flesh”—a living reality testifying of God’s grace—so must our communication have purpose and fulfillment. Because of its emphasis on building relationships through the communication process, leader–member exchange (LMX) theory provides a valid framework that describes how God demonstrated leadership and facilitated reconciliation with humanity through the Word. An exegetical analysis of John 1:1–18 considering LMX theory offered seven principles of effective communication.